EFFECT OF UREA FERTILIZER SUBSTITUTION WITH BIOSLURRY AND COW SLURRY OF GROWTH AND PRODUCTION OF Heteropogon contortus GRASS - A. A., Tifani; Suarna, I W.; witariadi, N. M. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
The effort to increase the productivity of Heteropogon contortus grass in particular can be done by giving organic fertilizer, one of which is fertilizer or waste result from the process of manufacture of biogas often referred as slurry and bio-slurry . The research aimed to find out the effect of substitution of urea fertilizer with bio-slurry and cow slurry towards growth and production Heterpogon contortus grass. The experiment using Completely Randomized Design (RAL) consisted of seven treatments and four replicates, therefore there were 28 units of experiments with doses; urea dose 200 kg/ha (A); urea dose 150 kg/ha + 5 tons/ha bio- slurry (B); urea dose 100 kg/ha + 10 tons/ha bio-slurry (C); urea dose 50 kg/ha + 15 tons/ha bio-slurry (D); urea dose 150 kg/ha + 5 tons/ha slurry (E); urea dose 100 kg/ha + 10 tons/ha slurry (F); urea dose 50 kg/ha + 15 tons/ha slurry (G). The observed variables include: plant height, number of leaves, number of branches, leaf dry weight, stem dry weight, root dry weight, total dry weight of forage, ratio with dry weight of stem, total dry weight ratio of forage with root dry weight ( top root ratio ), leaf areaand the amount of chlorophyll.  The results showedthat the substitution of urea fertilizer with bio-slurry and cow slurry can increase the growth and production of Heteropogon contortus grass . The use of urea dose ??200 kg/ha can be substitutewith urea dose 50 kg/ha in addition to 15 tons/ha of slurry fertilizer (G).   Keywords:  Urea, Bio-Slurry Of Cow, Sludge Slurry ,Growth , Production, Heteropogon contortu s